2022
DOI: 10.1111/mec.16760
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from microsatellites to SNP‐based microhaplotypes in genetic monitoring programmes: Lessons from paired data spanning 20 years

Abstract: Genetic monitoring quantifies trajectories of individual-and population-level metrics that include heterozygosity, gene diversity and genetic effective population size (N e ) over contemporary time series (Schwartz et al., 2007). Tracking these metrics facilitates adaptive and evolutionary-cognizant management. For the past three decades, microsatellites were the workhorse for genetic monitoring programmes (e.g., Beatty et al., 2014;Dowling et al., 2014;Koelewijn et al., 2010). Long-term monitoring programmes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 123 publications
2
7
0
Order By: Relevance
“…Generally, results support the conclusion that larger numbers of SNP loci provide greater power to resolve finer-scale spatial resolution in the genetic differences between individuals (Putman & Carbone, 2014;Thrasher et al, 2018;Osborne et al, 2022). This is particularly noticeable in STRUCTURE analysis of garden and wild Q. acerifolia individuals, where 10 garden samples are erroneously clustered using microsatellites.…”
Section: Population Differentiation and Assignmentsupporting
confidence: 62%
See 1 more Smart Citation
“…Generally, results support the conclusion that larger numbers of SNP loci provide greater power to resolve finer-scale spatial resolution in the genetic differences between individuals (Putman & Carbone, 2014;Thrasher et al, 2018;Osborne et al, 2022). This is particularly noticeable in STRUCTURE analysis of garden and wild Q. acerifolia individuals, where 10 garden samples are erroneously clustered using microsatellites.…”
Section: Population Differentiation and Assignmentsupporting
confidence: 62%
“…Genetic marker comparisons have largely demonstrated that broad measures of population differentiation generally correspond between microsatellites and SNPs, but the increased resolution of SNPs often allows for a more nuanced interpretation of population demography (Osborne et al., 2022; Putman & Carbone, 2014; Thrasher et al., 2018). The large number of SNP loci generated by RADseq approaches also allow for detection of subtle genetic distinctions even when only a few individuals are sampled (Jeffries et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A subtle, but progressive, shift in allele frequencies was also detected by DAPC in the period following the demographic bottleneck, particularly after 2016. This shift is corroborated by genome-wide single nucleotide polymorphism (SNP) data (Osborne et al, 2022). The recent reduction in allelic diversity highlights the need for adaptive management that capitalizes on years with favorable environmental conditions and high wild abundance (Table 3).…”
Section: Trajectory Of Genetic Diversitymentioning
confidence: 92%
“…We used NeEstimator (Do et al., 2014) to estimate linkage disequilibrium effective population size (LD N e ) with the single sample method (Hill, 1981) as described in Osborne et al. (2022). This method assumes a closed population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation